KONSEP PEMBINAAN AKHLAK DAN KESEHATAN MENTAL REMAJA PERSPEKTIF IMAM AL-GHAZALI - Salsabila, Anita Silmin; Tentiasih, Septyana (LPPM STAI Muhammadiyah Probolinggo, 2024)
Moral development and mental health have a close relationship with adolescents, including students. Basically, the manifestation of moral formation is not only about changes in attitudes that are visible physically but also the transformation of perspectives, mindsets, spirituality, and also feelings in a more positive direction. On the other hand, mental health issues are sometimes still considered not very important by our society. It turns out that it actually provides a lot of knowledge when examined further. Mental health will be achieved when a person's psychological condition is in a normal state in other words far from anxiety, fear, loneliness, anxiety, and emptiness. In fact, at the school level there are still many types of juvenile delinquency committed by students due to lack of understanding of morals. Not only that, today's teenagers also become more vulnerable to mental health problems due to various factors. Of course, this problem will be very worrying if it is not handled immediately duly. Therefore, in this paper will be discussed about Imam Al-Ghazali's point of view on the concept of moral formation and also mental health and how to apply it. Keywords: Moral Formation; Mental Healt; Imam Al-Ghazali.